The European Muslim Crisis and the Post-October 7 Escalation - Amin, Hira (Religions, 2024)
Israel’s war on Gaza following 7 October 2023 has given birth to several political and social changes in European nations. According to the United Nations Report of the Special Rapporteur, Israel has used this moment to “distort” international humanitarian law principles “in an attempt to legitimize genocidal violence against the Palestinian people.” In the European context, this has led to European Muslims and non-Muslims, including organizations, institutions, as well as individual academics, politicians, and activists mobilizing and voicing their condemnation and demand their governments to do more towards peaceful and equitable solutions. However, this has been met with a strong reaction from European governing bodies. This paper situates this reaction within wider discourses on the European Muslim crisis. It begins with a systematic literature review on the so-called European Muslim crisis, followed by case studies on the United Kingdom and Germany on their respective changes to policies impacting Muslims in the post-October 7 contexa Regarding the literature review, this paper illustrates how this concept has three distinct, yet intersecting meanings: the crisis of European identity; the crisis of foundational ideologies of Europe; and an internal Muslim crisis that often leads to radicalization. Through the British and German case studies, this paper illustrates that October 7 has reinforced and strengthened the shift towards values-based citizenship and integration. This paper argues that through branding pro-Palestine protesters and organizations as extremists in the British context, and adding questions related to antisemitism and Israel in the citizenship tests in the German context, the Israel/Palestine issue has now become yet another yardstick to demarcate the European, civilized “us” vs. the Muslim “other.” In doing so, October 7 has escalated elements already present within the wider discourses of the European Muslim crisis.